Role of Elongator Subunit Elp3 in Drosophila melanogaster Larval Development and Immunity - Walker, Jane (Genetics Society of America, 2011)
The Elongator complex has been implicated in several cellular processes, including gene expression and tRNA modification. We investigated the biological importance of the Elp3 gene in Drosophila melanogaster. Deletion of Elp3 results in larval lethality at the pupal stage. During early development, larval growth is dramatically impaired, with progression to the third instar delayed for ∼24 hr, and pupariation occurring only at day 14 after egg laying. Melanotic nodules appear after 4 days. Microarray analysis shows that stress response genes are induced and ecdysone-induced transcription factors are severely repressed in the mutant. Interestingly, the phenotypes of Elp3 flies are similar to those of flies lacking the domino gene, encoding a SWI/SNF-like ATP-dependent chromatin-remodeling enzyme. Indeed, the gene expression profiles of these mutants are also remarkably similar. Together, these data demonstrate that Drosophila Elp3 is essential for viability, normal development, and hematopoiesis and suggest a functional overlap with the chromatin remodeler Domino.